EMERGING TRENDS IN HOSPITALITY AND TOURISM - Rao, R.Srinivasa (International Journal of Research -GRANTHAALAYAH, 2014)
The hospitality and tourism industry has changed more than a little since the first motel, in San Luis Obispo, California, was opened in 1925. (Its rooms went for 2.50 a night.) Today, there are more than four million guest rooms in the country, and tourists and businesspeople spend about 550 billion each year on travel in the United States As a vast and growing industry, hospitality and tourism provides more opportunities for ambitious educated and uneducated persons who enjoy working with people. The hospitality and tourism industry working in a more competitive environment. It is essential that those seeking careers as successful professionals develop a strong business foundation and customer service skills. There are few main themes are to be required to promote the hospitality and tourism industry such as international tourism planning; the development and operation of hotels; Europe and the Single Market; planning issues and techniques; service improvement; finance and performance; and the psychology of management. The purpose of this study is to identify, analyze, and noted the future trends that has been done tat now related to hospitality and tourism sector. This kind of study will be helpful to identify both the advancement and some gaps in this field, thus help to establish a more efficient, effective, and accountable tourism research to support practical work.